Beauty in the Eye of the Holder: The Contribution of Body Appreciation to Sexual Health in Adult Women - Robbins, Anne-Rose (Université d'Ottawa / University of Ottawa, 2017)
Perhaps one of the most embodied of human experiences, sexuality can be greatly affected by the way in which women perceive their body. Historically, scholars have dedicated their attention to negative facets of body image and how it is associated with poorer female sexual health, while mostly overlooking the positive aspects of this relationship. Similarly, although ageing is a key factor to consider when examining body image and sexual health, only a dearth of studies has attempted to describe the experiences of non-university aged women. To fill these gaps, this research program was designed to investigate the associations between positive and negative aspects of body image and explore how each contributes to sexual health in age-varied samples of adult women. Two survey studies were carried out. A total of 215 heterosexual women, aged 18 to 88, participated in the first study. Despite a high statistical overlap between body appreciation (i.e., positive body image) and body dissatisfaction (i.e., negative body image), the former was found to be a greater contributing factor to indicators of sexual health. Specifically, body appreciation was related to improved sexual function, lower sexuality-related distress, and higher sexual satisfaction, even when controlling for body mass index. Although many changes occur to the body as women get older, body appreciation was unrelated to age in this sample. Nevertheless, it was shown to moderate the negative association between age and sexual satisfaction, such that older women with high appreciation for their body reported being significantly more sexually satisfied than those with low body appreciation. While the first study explored the body image and sexual health experiences of adult women in general, the second article focused on the mechanisms through which one is related to the other in midlife and older women specifically. A total of 193 heterosexual women, aged 50 to 83, completed an online survey. Support was provided for the use of objectification theory (Frederickson & Roberts, 1997), a well-established theoretical framework in body image research, in explaining sexual health in midlife and older women. Body self-consciousness during sex partially explained the relationship between body shame, appearance anxiety, and sexual function, distress, and satisfaction. High body appreciation mitigated the detrimental effect of self-objectification constructs (i.e., body surveillance, appearance anxiety) and body self-consciousness during sex on midlife and older women's sexual health. Overall, based on the results of this dissertation, body appreciation appears to serve as a protective factor for improved sexual health. Similar to sexual satisfaction and sexual distress, positive and negative aspects of body image are related, but nonetheless distinct, concepts that should not be used interchangeably. Furthermore, midlife and older women's body image and sexual experiences differ from that of their younger counterparts; systematic generalisation of findings from one group to the other is thus unwarranted. Consideration for these various distinctions is not only required for increased understanding of the complex links between body image and sexuality across adulthood, but also relevant to guide prevention efforts at a sociocultural level and clinical interventions at the individual level.
Keywords: Body Image; Sexual Health; Female Sexual Function; Body Appreciation; Sexual Satisfaction; Sexual Distress